2016
DOI: 10.1002/ajh.24263
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐transplant clostridium difficile infections in patients undergoing allogeneic hematopoietic progenitor cell transplant

Abstract: Clostridium difficile infections (CDI) remain the leading cause of infectious diarrhea among hospitalized patients in this country. Patients with hematologic malignancies, especially those who undergo hematopoietic progenitor cell transplants are particularly at risk for developing CDI. One hundred and forty seven consecutive allogeneic hematopoietic progenitor cell transplants were analyzed for peri-transplant Clostridium difficile infections (PT-CDI). Sixteen patients (11%) developed PT-CDI (Median time 5 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…CDI in patients who underwent allogeneic HSCT was not associated with any increased risk of mortality . There are several reported risk factors for the incidence of CDI following allogeneic HSCT, including carbapenem use, previous C difficile colonization, CDI within nine months before allogeneic HSCT, total body irradiation, cord blood transplant, and onset of acute GVHD up to one year after allogeneic HSCT .…”
Section: Intestinal Dysbiosis and Clostridium Difficile Infection Folmentioning
confidence: 90%
See 1 more Smart Citation
“…CDI in patients who underwent allogeneic HSCT was not associated with any increased risk of mortality . There are several reported risk factors for the incidence of CDI following allogeneic HSCT, including carbapenem use, previous C difficile colonization, CDI within nine months before allogeneic HSCT, total body irradiation, cord blood transplant, and onset of acute GVHD up to one year after allogeneic HSCT .…”
Section: Intestinal Dysbiosis and Clostridium Difficile Infection Folmentioning
confidence: 90%
“…A discussion of the effects of a disrupted intestinal microbiome on the development of GVHD following allogeneic HSCT is not complete without including C difficile infection (CDI) since both diseases are related to intestinal dysbiosis and the presence of one affects the development of the other. CDI is one of the most commonly observed complications following allogeneic HSCT, estimated to occur in 10% to 15% of patients . With the emergence of the more virulent NAP‐1/027 strain, the incidence of CDI is expected to increase rapidly.…”
Section: Intestinal Dysbiosis and Clostridium Difficile Infection Folmentioning
confidence: 99%
“…A study by Jain et al found that 12 percent of patients admitted to their institution for SCT were colonized with toxigenic C. difficile [14]. Agha et al reported that 11 percent of SCT recipients developed peri-transplant CDI [15]. Interestingly, the only factor independently associated with development of CDI was a previous history of the same.…”
Section: Main Textmentioning
confidence: 99%
“…Interestingly, the only factor independently associated with development of CDI was a previous history of the same. Patients with matched-related grafts had a lower likelihood of developing CDI in the study population [15]. A review by Alonso et al found an overall CDI rate of 9.2% among SCT recipients, with higher rates among allogeneic transplant recipients compared to those who underwent autologous transplant (12.5 vs. 6.5%) [11, 12].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation